Comparative evaluation of sealing ability of two self-adhesive flowable composites following various restorative techniques in Class V lesions: An in vitro study - Mishra, Raman; Sarangi, Priyanka; Mallick, Rashmi Rekha; Punjabi, Mansi; Satapathy, Sukanta Kumar; Sheetal, Kotni (Bangladesh Journal of Medical Science, 2024)
Background: Class V lesions present a clinical challenge due to their location at the cervical region of teeth, where factors such as microleakage and polymerization shrinkage can compromise the longevity of restorations. Self-adhesive flowable composites offer the advantage of simplified application, but their sealing ability may vary based on different restorative techniques. This in vitro study aimed to compare the sealing ability of two self-adhesive flowable composites, Clearfil S3 Universal and G-Premio Bond, when applied using various restorative techniques in Class V lesions. Materials and Methods: Eighty extracted human premolars were selected and randomly divided into two groups, with each group treated with one of the two self-adhesive flowable composites. Class V cavities were prepared on the buccal surfaces of the teeth. Four restorative techniques were employed: Group A - Direct application of the composite; Group B - Application of the composite with a bonding agent (Clearfil SE Bond); Group C - Application of the composite with selective enamel etching; Group D - Application of the composite with a dentin adhesive (G-Premio Bond) and selective enamel etching. After restoration, the teeth were subjected to thermocycling, immersed in methylene blue dye, sectioned, and evaluated for dye penetration under a stereomicroscope. The extent of dye penetration was quantified and statistically analyzed.Results:The results showed that Group D, where G-Premio Bond was used with selective enamel etching, demonstrated the least dye penetration (mean value X) compared to the other groups (X1, X2, X3). The differences in sealing ability between the groups were statistically significant (p < 0.05). Clearfil S3 Universal showed better sealing ability when used with a bonding agent (Group B) compared to direct application (Group A). Conclusion: In Class V restorations, the choice of self-adhesive flowable composite and restorative technique significantly affects sealing ability. G-Premio Bond, in combination with selective enamel etching, provided superior sealing compared to other techniques. Clearfil S3 Universal performed better when used with a bonding agent. These findings highlight the importance of selecting the appropriate material and technique for Class V restorations to minimize microleakage and improve clinical outcomes. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S92-S96